2002
DOI: 10.1017/s0022112002002574
|View full text |Cite
|
Sign up to set email alerts
|

Wall turbulence manipulation by large-scale streamwise vortices

Abstract: This paper describes an experimental study of the manipulation of a fully developed turbulent channel flow through large-scale streamwise vortices originated by vortex generator jets distributed along the wall in the spanwise direction. Apart from the interest in flow management itself, an important aim of the research is to observe the response of the flow to external perturbations as a technique for investigating the structure of turbulence. Considerable mean and fluctuating skin friction reductions, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 34 publications
(57 reference statements)
4
42
4
Order By: Relevance
“…Indeed, Willis, Hwang & Cossu (2009 have forced large-scale linearly optimal α = 0 vortices, computed with the same approach used in this study, in a DNS of the turbulent pipe flow. A large amplification of the forcing is observed and the induced large-scale finite-amplitude streaks modify the flow at leading order and induce a reduction of the turbulent drag consistently with the results of Schoppa & Hussain (1998) (plane channel flow, DNS) and Iuso et al (2002) (boundary layer, experimental results).…”
Section: Relevance Of the Harmonic Forcing Analysissupporting
confidence: 80%
“…Indeed, Willis, Hwang & Cossu (2009 have forced large-scale linearly optimal α = 0 vortices, computed with the same approach used in this study, in a DNS of the turbulent pipe flow. A large amplification of the forcing is observed and the induced large-scale finite-amplitude streaks modify the flow at leading order and induce a reduction of the turbulent drag consistently with the results of Schoppa & Hussain (1998) (plane channel flow, DNS) and Iuso et al (2002) (boundary layer, experimental results).…”
Section: Relevance Of the Harmonic Forcing Analysissupporting
confidence: 80%
“…In their experiment using jets to create streamwise vortices in a channel flow, Iuso et al 22 observed a similar shift in the power spectra of the streamwise velocity signal towards the lower frequencies when drag reduction occurs. In studies on polymer additives for drag reduction, similar shifts in the power spectra are often observed together with drag reduction.…”
Section: Power Spectral Measurementsmentioning
confidence: 80%
“…Streamwise vorticity can be effective in introducing spanwise flow components near the wall. 21,22 Choi et al 19 and Schoppa and Hussain 21 have shown that it takes very small spanwise flow components to be introduced to result in significant skin friction drag reduction. Unlike riblets, the introduction of spanwise flow components can result in skin friction reductions of up to 40% under optimum flow conditions.…”
Section: Power Spectral Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data were obtained in a previous control experiment of wall bounded turbulence in a channel flow [35], which the reader is referred to for a full description of the experimental setup and the conditions. The half channel height h is equal to 10 mm and the span of the test section is such that the aspect ratio width/height is equal to 14.…”
Section: Experimental Setup and Definitionsmentioning
confidence: 99%